Exploration of biological concept understanding through augmented reality: A constructivism theory approach - Muhammad Zahrudin Afnan; Rinie Pratiwi Puspitawati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Augmented reality (AR) technology combines real-world environments with digital elements, creating interactive experiences that enhance student learning. AR has significant educational potential, allowing students to visualize and interact with abstract concepts across various subjects, including economics, biology, and physics. This qualitative study explores the potential of Augmented Reality (AR) in enhancing the understanding of biological concepts through the lens of constructivism theory. The research aims to investigate how AR technology can be leveraged to create immersive and interactive learning experiences in biology education. By examining the perspectives of educators, students, and AR developers, this study seeks to provide insights into the effectiveness of AR in constructing knowledge and promoting deeper comprehension of complex biological processes. This research uses a qualitative approach with a literature study method and descriptive analysis to explore the understanding of biological concepts through Augmented Reality (AR) from the perspective of constructivism theory.Augmented Reality (AR) is revolutionizing educational paradigms by creating immersive learning environments that blend physical and digital elements, This technology supports the constructivist learning theory by allowing students to actively construct knowledge through direct interaction with virtual biological models, fostering deeper comprehension of complex biological systems and processes.While AR presents significant educational potential, its implementation in biology education faces several challenges that require careful consideration and strategic solutions. AR can help students understand complex concepts in a more exciting and fun way. In the context of constructivism theory, AR supports active, collaborative, and experience-based learning, which is very important in biology education.